Impact of expressive suppression on subthreshold depression among college students: a moderated mediation model - Chen, Mingxuan; Huang, Lieyu; Qin, Qian; Li, Jinlu; Zhang, Jiarui; Ma, Jing; Song, Haoyang (Frontiers in Psychology, 2025)
IntroductionEmotion regulation strategies, particularly expressive suppression, and negative attention bias significantly contribute to the onset and persistence of subthreshold depression among college students. However, the underlying moderating mechanisms of this relationship remain inadequately understood. Guided by the Emotion Regulation Process Model, this study examined a moderated mediation model to determine whether negative attention bias mediates the relationship between expressive suppression and subthreshold depression and to explore the moderating role of regulatory emotional self-efficacy within this framework.MethodsA total of 956 college students aged between 19 and 24 years participated in this cross-sectional survey.ResultsNegative attention bias fully mediated the relationship between expressive suppression and subthreshold depression. Moreover, regulatory emotional self-efficacy moderated both the direct relationship between expressive suppression and subthreshold depression, and the association between negative attention bias and subthreshold depression. Specifically, individuals with higher levels of regulatory emotional self-efficacy exhibited diminished indirect effects of expressive suppression on subthreshold depression through negative attention bias.DiscussionThese findings provide valuable insights into potential mechanisms for targeted interventions and preventative measures aimed at reducing depressive symptoms among college students.